Randomised controlled trial of effects of early discharge after surgery for breast cancer. Issue 7168 (7th November 1998) - Bundred, Nigel; Maguire, Peter; Reynolds, Jill; Grimshaw, Jill; Morris, Julie; Thomson, Lesley; Barr, Lester; Baildam, Andrew
Abstract : Abstract: Objective : To determine the effect of early discharge from hospital after surgery for breast cancer on physical and psychological illness. Design : Randomised controlled trial comparing discharge two days after surgery (before removal of drain) with standard management (discharge after removal of drain). Setting : Regional breast unit. Subjects : 100 women with early breast cancer undergoing mastectomy and axillary node clearance (20) or breast conservation surgery (80). Main outcome measures : Physical illness (infection, seroma formation, shoulder movement) and psychological illness (checklist of concerns, Rotterdam symptom questionnaire, hospital anxiety and depression scale) preoperatively and at one month and three months postoperatively. Results : Women discharged early had greater shoulder movement (odds ratio 0.28 (95% confidence interval 0.08 to 0.95); P=0.042) and less wound pain (odds ratio 0.28 (0.10 to 0.79); P=0.016) three months after surgery compared with women given standard management. One month after surgery scores were significantly lower on the Rotterdam symptom questionnaire in patients who were discharged early (ratio of geometric mean scores 0.73 (0.55 to 0.98); P=0.035), but rates of psychological illness generally did not differ between groups. Conclusions : Increased rates of physical or psychological illness did not result from early discharge after surgery for breast cancer. This policy can be recommended for patients with support at home.